Interferon-β decreases LPS-induced neutrophil recruitment to cardiac fibroblasts - Anfossi, Renatto; Vivar, Raúl; Ayala, Pedro; González-Herrera, Fabiola; Espinoza-Pérez, Claudio; Osorio, José Miguel; Román-Torres, Mauricio; Bolívar, Samir; Díaz-Araya, Guillermo (Frontiers in Cell and Developmental Biology, 2023)
Cardiac fibroblasts (CF) have been recognized as sentinel cells due to their regulatory functions on the inflammatory infiltrate cells in damaged tissues. CF expresses TLR4 and secretes pro-inflammatory mediators; it also secretes, and responds to interferon-β (IFN-β), which has been shown to modulate the inflammatory response of CF. We have shown that CF interacts with immune cells; however, CF interaction with neutrophils has not been studied in depth. The effects of lipopolysaccharide (LPS) and/or IFN-β on CF-neutrophil interaction are poorly understood. CF isolated from adult Sprague-Dawley rats were treated with LPS in the presence/absence of IFN-β. IL-8 secretion, ICAM-1 and VCAM-1 expression, recruitment of neutrophils, and the consequences of CF-neutrophil interaction on MMPs activity were also evaluated. The results show that LPS induced an increase in IL-8 expression and secretion; and in ICAM-1 and VCAM-1 expression. These effects of LPS were blocked by TAK-242. Pretreatment of CF with IFN-β prevented these effects of LPS on CF. In LPS-treated CF, neutrophil recruitment was increased and the pre-treatment with IFN-β prevented LPS effects. The anti-inflammatory effects of IFN-β were blocked by ruxolitinib, a JAK inhibitor, suggesting that the effect of IFN-β is mediated via JAK. Analysis of zymograms of the culture medium from CF alone, treated CF co-cultured with adherent neutrophils, showed that MMP2 was mainly derived from CF, whereas MMP9 could be derived from neutrophils. In CF alone, both LPS and IFN-β treatment increased the secretion of MMP2. CF alone showed low MMP9 activity, and LPS or IFN-β did not change MMP9 activities. When CF were previously pre-treated with LPS, IFN-β and IFN-β + LPS and then co-cultured with neutrophils, an increase in MMP2 was observed. In CF co-cultured with neutrophils, an increase in MMP9 activity was observed, although these effects were less pronounced in CF pre-treated with IFN-β, where a decrease in MMP9 was observed with respect to unstimulated CF.Conclusions: . Our results highlight that interaction between CF and neutrophils could play a key role in modifying the extracellular matrix by altering MMPs activity.